Hubungan Pengetahuan dengan Kecemasan pada Pasien Pre Operasi Katarak di Rumah Sakit B - Dwi Alba Fitria; Ayu My Lestari Saragih; Irfan Ilmi; Nurdewi Sulymbona (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
In the pre-operative period, patients feel afraid, anxious, nervous and insecure, afraid that their vision will not heal completely, afraid of unwanted complications. This feeling arises due to lack of knowledge or inadequate information and expected results after surgery. This study aims to determine the relationship between knowledge and anxiety in patients during pre-cataract surgery at Hospital B. Quantitative research with descriptive correlation design with a cross-sectional approach with a non-probably sampling technique, namely purposive sampling with a total of 41 respondents. Data collection through questionnaires, data were analyzed univariately with frequency distribution and bivariate correlation using the Spearman Rank correlation test. The majority of respondents with a good level of knowledge were 25 respondents (61%), most of whom had mild anxiety were 23 respondents (56.1%). From the results of the analysis with Spearman Rank correlation (rho) using the SPSS 24 for windows application, the results of the correlation coefficient between knowledge and anxiety in pre-operative patients were -0.448. This shows that there is a strong correlation between the relationship between knowledge and anxiety with a negative relationship direction, which means that the higher the patient's level of knowledge, the lower the patient's level of anxiety during pre-cataract surgery. With the result of p = 0.003, then p <0.05, this also shows that there is a relationship between knowledge and anxiety in patients during pre-surgery at Hospital B